2005
DOI: 10.1073/pnas.0504420102
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42GAP regulates c-Jun N-terminal kinase (JNK)-mediated apoptosis and cell number during mammalian perinatal growth

Abstract: Rho family GTPase Cdc42 is known to regulate polarity and growth in lower eukaryotes, but its physiologic function in mammals has yet to be determined. Here we have disrupted cdc42gap, a ubiquitously expressed negative regulator of Cdc42, in mice. Cdc42GAP ؊/؊ embryonic fibroblasts and various organs displayed significantly elevated Cdc42 activity. The embryonic and neonatal homozygous mice were reduced in size by Ϸ25-40% and suffered severe growth retardation. Major organs from Cdc42GAP ؊/؊ mice were proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 32 publications
(40 reference statements)
6
57
0
Order By: Relevance
“…The current Cdc42 conditional knockout model reveals unique HSC regulatory functions of Cdc42 that are not predictable in the Cdc42 gain-of-activity Cdc42GAP Ϫ/Ϫ mice (13,23,24). Although Cdc42GAP Ϫ/Ϫ hematopoietic progenitors show normal cell cycle progression but increased apoptosis due to increased JNK activity, Cdc42 Ϫ/Ϫ HSCs display drastically increased cell cycle progression/entry but unaltered survival property.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current Cdc42 conditional knockout model reveals unique HSC regulatory functions of Cdc42 that are not predictable in the Cdc42 gain-of-activity Cdc42GAP Ϫ/Ϫ mice (13,23,24). Although Cdc42GAP Ϫ/Ϫ hematopoietic progenitors show normal cell cycle progression but increased apoptosis due to increased JNK activity, Cdc42 Ϫ/Ϫ HSCs display drastically increased cell cycle progression/entry but unaltered survival property.…”
Section: Resultsmentioning
confidence: 99%
“…Because HSCs need to detach from the niche where they are maintained at a quiescent state and migrate to a proliferative zone to enter into asymmetric division and expansion (23), it is believed that HSC interaction with the niche microenvironment and HSC quiescent state maintenance are closely interconnected. The present study shows that deletion of Cdc42 reduces the number and frequency of quiescent HSCs and increases the stem/progenitor population that is actively cycling.…”
Section: Resultsmentioning
confidence: 99%
“…In primary MEFs, however, Cdc42 activity is critical for cell proliferation, as loss or gain of activity of Cdc42 affects cell cycle progression and/or survival ( Figure 7; Wang et al, 2005). The cell growth defects of the Cdc42 Ϫ/Ϫ cells correlate with defects in ERK1/2, JNK, and/or p70S6K activity, and with a defect in transcriptional activation of NF-B (Figures 8 and 9).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, those few studies commonly reported that the ablation of a specific GAP resulted in the global elevation of the activity of the target small GTPase (49,57,58); Rho GTP levels were highly elevated in P190B RhoGAP null murine embryonic fibroblasts (49), as was the Cdc42 GTP level in Cdc42GAP null murine embryonic fibroblasts and hematopoietic stem cells (57,58). Those studies also reported changes in the overall size of the cells or the whole animal as well as in the growth of cells (49,57,58). However, we did not see any difference in basal Rac GTP levels among bcr Ϫ/Ϫ , abr Ϫ/Ϫ , and (abr ϫ bcr) Ϫ/Ϫ BMMs, nor did we observe any change in the overall cell size of BMMs or the whole animal (data not shown).…”
Section: Discussionmentioning
confidence: 99%